Obesity And Graves’Disease, Possible Association (Journal of Pharmaceutical Negative Results, 2022)
Graves’ disease is an autoimmune disease causing hyperthyroidism and goiter in most cases. As thyroid hormone controls bodymetabolism, so extra thyroid hormone could be associated with a high basal metabolic rate, leading to weight loss. But in some casesof hyperthyroidism there is a weight gain development instead of weight loss. The present study was conducted on (101) patientsalready diagnosed with Graves’ disease for evaluating there TSH levels and its relation with BMI. The results show that about threequarters of the sample gender ware females (72.28%) and about (48.5%) of total cases have obesity, (19.8%) have over weight with asignificant correlation between TSH levels and BMI.